Evaluation of three diagnostic algorithms to reduce normal scan rates, radiation exposure and costs in patients with suspected chronic coronary syndrome referred for 82Rb-Positron Emission Tomography (82Rb-PET) - Christian Müller; Damian Wild; Philip Haaf; Felix Mahfoud; Michael J Zellweger; Simon M Frey; Gabrielle Huré; Jan-Philipp Leibfarth; Kathrin Thommen; Melissa L Amrein; Ibrahim Schaefer; Klara Rumora; et al. (Open Heart)
Background The majority of functional ischemia tests in patients with suspected chronic coronary syndromes (CCS) yield normal results. Implementing gatekeepers for patient preselection, such as pretest probability (PTP) and/or coronary artery calcium score (CACS), could reduce the number of normal scan results, radiation exposure and costs. However, the efficacy and safety of these approaches remain unclear.Methods Three diagnostic algorithms based on PTP, as summarised in the 2019 European Society of Cardiology (ESC) CCS guidelines, were retrospectively applied to 1792 patients with suspected CCS referred for 82Rb-Positron Emission Tomography (82Rb-PET): (1) defer testing if PTP ≤5%; (2) defer if PTP <15%; and (3) defer if PTP ≤5% or PTP 5–15% and CACS 0. The proportion of missed ischemia, number of scans and reduction of normal scan results, radiation exposure and costs were compared with the current gold standard (CACS+PET in every patient). Endpoints were defined as small ischemia (SDS ≥2) and relevant ischemia (≥10% of myocardium).Results The mean age of the patients was 65±11 years, and 43% were female. PTP ≤5% and <15% were present in 7.5% and 41.0%, respectively. Algorithm 1 reduced scans, radiation and costs by 7.5% without significantly missing ischemia (sensitivity/negative predictive value (NPV) 98.6%/99.7%). Algorithm 2 showed the largest reduction (41.0%), but sensitivity was significantly reduced (80.2%). Algorithm 3 demonstrated optimal performance, reducing radiation by 17.0% and costs by 17.3% without significantly missing ischemia suggesting excellent safety (sensitivity/NPV 98.0%/99.5%).Conclusion Using a diagnostic algorithm combining PTP and CACS (algorithm 3), the number of normal scan results, radiation exposure and costs could be significantly reduced without a significant increase in missed diagnoses suggesting similar outcome and excellent patients safety. Consequently, this approach could help to optimally allocate limited healthcare resources while maintaining patient’s safety.